2018
DOI: 10.18632/oncotarget.25003
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR complex 2 restrains tumor angiogenesis in multiple myeloma

Abstract: The mammalian Target of Rapamycin (mTOR) is an intracellular serine/threonine kinase that mediates intracellular metabolism, cell survival and actin rearrangement. mTOR is made of two independent complexes, mTORC1 and mTORC2, activated by the scaffold proteins RAPTOR and RICTOR, respectively. The activation of mTORC1 triggers protein synthesis and autophagy inhibition, while mTORC2 activation promotes progression, survival, actin reorganization, and drug resistance through AKT hyper-phosphorylation on Ser473. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 55 publications
1
50
0
Order By: Relevance
“…It has been shown that selective or targeted mTORC2 inhibition causes reduced cell proliferation, tumor size, and angiogenesis in several types of cancers including colon cancer, breast cancer and multiple myeloma [49][50][51][52][53]. Differential effects of dose-interval schedules of rapamycin (or rapalogs) on colon cancer have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that selective or targeted mTORC2 inhibition causes reduced cell proliferation, tumor size, and angiogenesis in several types of cancers including colon cancer, breast cancer and multiple myeloma [49][50][51][52][53]. Differential effects of dose-interval schedules of rapamycin (or rapalogs) on colon cancer have also been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Signals for angiogenesis include angiopoietin, interleukin (IL) 8, FGF, VEGF, and PDGF. PI3K-AKT signaling pathway regulates angiogenesis induction and stabilization of the vessel [119], with potential multifaced therapeutic windows in a broad spectrum of malignancies [186,187]. In addition, HIF1 stimulates the synthesis and secretion of VEGF in cancer cells.…”
Section: Angiogenesismentioning
confidence: 99%
“…The mammalian target of rapamycin (mTOR) is an intracellular serine/threonine kinase that mediates intracellular metabolism, cell survival, and actin rearrangement. mTOR is made of two independent complexes, mTORC1, involved in protein synthesis and autophagy inhibition, and mTORC2, involved in progression promotion, survival, actin reorganization, and drug resistance [125][126][127]. In MM endothelial, a significantly higher activation of mTORC2 have been demonstrated.…”
Section: Soluble Factors and Transduction Pathwaysmentioning
confidence: 99%
“…In MM endothelial, a significantly higher activation of mTORC2 have been demonstrated. Its inhibition induces a reduction of the angiogenic abilities of MM endothelial cells, suggesting a major role of mTORC2 in the "angiogenic switch" and indicates that mTORC2 might be a new antiangiogenic target in MM [127].…”
Section: Soluble Factors and Transduction Pathwaysmentioning
confidence: 99%